2007
DOI: 10.2208/proce1989.54.1226
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Pollutant Load in the Edo River, Ara River and Tama River.

Abstract: To clarify water quality and pollutant loads in the Edo, Ara and Tama Rivers, we examine the temporal changes of water pollution using monitoring data obtained by local governments and continuous monitoring data for COD. We also evaluate yearly-averaged SS, COD, T-N and T-P fluxes in these rivers by conducting the field measurements under several hydrologic events. The trend analysis for COD continuously monitored in the Edo River indicates that the changes of COD under low flow conditions are not similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Arakawa River, which is the largest river flowing into the bay, accounts for about 30 % of the freshwater discharge (Nihei et al, 2007a). Most rivers flowing into the bay have similar water quality because of similar land use within the drainage basin (Nihei et al, 2007b); accordingly, we can reasonably assume that observed RDOC and BDOC concentrations at the lower Arakawa River station represent concentrations of total river water flowing into Tokyo Bay. Table 2 summarizes the first-order decay constants obtained by fitting the exponential degradation of DOC with time.…”
Section: Lability and Sources Of Freshwater Doc Flowing Into Tokyo Baymentioning
confidence: 98%
“…Arakawa River, which is the largest river flowing into the bay, accounts for about 30 % of the freshwater discharge (Nihei et al, 2007a). Most rivers flowing into the bay have similar water quality because of similar land use within the drainage basin (Nihei et al, 2007b); accordingly, we can reasonably assume that observed RDOC and BDOC concentrations at the lower Arakawa River station represent concentrations of total river water flowing into Tokyo Bay. Table 2 summarizes the first-order decay constants obtained by fitting the exponential degradation of DOC with time.…”
Section: Lability and Sources Of Freshwater Doc Flowing Into Tokyo Baymentioning
confidence: 98%
“…Arakawa River, which is the largest river flowing into the bay, accounts for about 30 % of the freshwater discharge (Nihei et al, 2007a). Most rivers flowing into the bay have similar water quality because of similar land use within the drainage basin (Nihei et al, 2007b); accordingly, we can reasonably assume that observed RDOC and BDOC concentrations at the lower Arakawa River station represent concentrations of total river water flowing into Tokyo Bay.…”
Section: Lability and Sources Of Freshwater Doc Flowing Into Tokyo Baymentioning
confidence: 98%